HUBUNGAN WORK-FAMILY CONFLICT DENGAN KEPUASAN PERNIKAHAN PADA ISTRI YANG MENJADI TULANG PUNGGUNG KELUARGA DI DESA JELEGONG RANCAEKEK - Fitria Rizqi Anggarwati; Dyah Rachman Kuswartanti; Nida Muthi Annisa (LPPM UNIBI, 2022)
A working wife will have an impact on the emergence of work-family conflict on the wife and this will be related to the wife's satisfaction with her marriage. This study aims to determine the relationship between work-family conflict and marital satisfaction for the wife who is breadwinner of the family at Jelegong Rancaekek village. Respondents in this study amounted to 75 wifes with the criteria; living in Jelegong Rancaekek Village, working and being the breadwinner and living in the same house with their husband. The method of research used quantitative with correlational research. The population and sample technique used is population research, the data collection method used a questionnaire in the form of a questionnaire and the research using two measuring, namely the work-family conflict measurement (WFC) and the marital satisfaction measurement (ENRICH). The data analysis technique used in this study uses the product-moment technique with the help of SPSS version 22. Based on the results of data analysis, the significance level is 0.000 with a correlation value of 0.722. This shows that work-family conflict has a positive relationship with marital satisfaction for the wife who is the breadwinner of the family in Jelegong Rancaekek Village, so it can be interpreted that the higher the work-family conflict, the marital satisfaction will increase, and vice versa.